Prevalence of Conventional Cardiovascular Risk Factors in Patients with Acute Coronary Syndrome - Abreu, G (2015)
Background: Primary prevention studies have shown that early detection and aggressive treatment of cardiovascular risk factors (CRF) prevent cardiovascular events. It is not well described the prevalence of CRF in patients, at the moment of admission due to acute coronary syndrome (ACS). Aim: To determine the prevalence of CRF among patients admitted with ACS. Methods: We analysed 4871 patients admitted consecutively in our coronary care unit with a diagnosis of ACS and included in a prospective registry, from January 2002 to October 2013. We studied the prevalence of conventional risk factors (diabetes, hypertension, smoking, dyslipidaemia) and compared findings according to gender and type of ACS: ACS with ST elevation (STEMI), ACS without ST elevation (NSTEMI). Results: Men represented 75% (n=3658) of the total population, were younger than women (61.6±12,9 vs 70.9 ±11.8 years; p<0.001) and had more frequently body mass index ≥ 25 kg/m2 (70.9% vs 62.3%; p<0.001). The most frequent CRF was hypertension (62.4%; n=3038), followed by dyslipidaemia (50.6%, n=2467), smoking (43.2%; n=2106) and diabetes (27.2%; n=1324). In women, the more common CRF were hypertension (75%) and dyslipidaemia (51.2%), whereas in men were smoking (54.4%) and dyslipidaemia (50.5%). We identify, at least, one CRF in 92,4% of all patients and two or three risk factors in 58.1%. Women had more frequently 2 CRF than men (40.1% vs 36.3%; p=0.011), although mean had, more often, 4 CRF (8.9% vs 4.1%; p<0.001). Previous history of cerebrovascular disease was more observed in women (8.6% vs 6.1%; p=0.002), but men had more often history of previous revascularization (9.8% vs 6.8%; p<0.001). On admission men presented more frequently STEMI (50.8% vs 43.5%; p<0,001) and less frequently renal dysfunction (17.2% vs 39.6%; p<0.001) and anaemia (18.8% vs 33.3%; p<0.001). Hypertension was the most prevalent CFR as in patients STEMI (56.6%) as in NSTEMI patients (67.9%), followed by smoking (47.5%) in STEMI patients and by dyslipidaemia (55.7%) in NSTEMI patients. Conclusion: We found at least one CRF in 92.8% of patients and two or three in more than half. Hypertension emerged as the major CRF in both forms of presentation of ACS.